ChemInform Abstract: A Practical, Chemoselective Approach to O‐Methylation of Carboxylic Acids with Dimethyl Malonate. Issue 10 (February 2016) - Mao, Jincheng; Liu, Defu; Li, Yongming; Zhao, Jinzhou; Rong, Guangwei; Yan, Hong; Zhang, Guoqi
Abstract: The scalable protocol is successfully applied to variously functionalized aryl, hetaryl, and alkenyl substituted carboxylic acids as well as N‐protected amino acids and dicarboxylic acids, but fails using propiolic acids.